Ex vivo electroretinograms made easy: performing ERGs using 3D printed components. (26th September 2020) - Bonezzi, Paul J.; Tarchick, Matthew J.; Renna, Jordan M.
Abstract : Key points: Rod and cone photoreceptors convert light into electrochemical signals that are transferred to second order cells, initiating image‐forming visual processing. Electroretinograms (ERGs) can detect the associated light‐induced extracellular transretinal events, allowing for physiological assessment of cellular activity from morphologically intact retinas. We outline a method for economically configuring a traditional patch‐clamp rig for performing high signal‐to‐noise ex vivo ERGs. We accomplish this by incorporating various 3D printed components and by modifying existing light pathways in a typical patch‐clamp rig. This methodology provides an additional set of tools to labs interested in studying the physiological function of neuronal populations in isolated retinal tissue. Abstract: Rod and cone photoreceptors of the retina are responsible for the initial stages in vision and convey sensory information regarding our visual world across a wide range of lighting conditions. These photoreceptors hyperpolarize in the presence of light and subsequently transmit signals to second‐order bipolar and horizontal cells. The electrical components of these events are experimentally detectable, and in conjunction with pharmacological agents, can be further separated into their respective cellular contributions using electroretinograms (ERGs). Extracellular activity from populations of rods and cones generate the negative‐going a‐wave, while ON‐bipolar cells generate positive‐going b‐waves. ERGs can be performed in vivo or alternatively using an ex vivo configuration, where retinas are isolated and transretinal photovoltages are recorded at high signal‐to‐noise ratios. However, most ERG set‐ups require their own unique set of tools. We demonstrate how, at low cost, to reconfigure a typical patch‐clamp rig for ERG recordings. The bulk of these modifications require implementation of various 3D printed components, which can alternatively aid in generating a stand‐alone ERG set‐up without a patch‐rig. Further, we discuss how to configure an ERG system without a patch‐clamp rig. Compared to in vivo ERGs, these are superior when measuring small responses, such as those that are cone‐evoked or those from immature mouse retinae. This recording configuration provides high signal‐to‐noise detection of a‐waves (300–600 µV) and b‐waves (1–3 mV), and is ultimately capable of discerning small (1–2 µV) photovoltages from noise. These quick and economical modifications allow researchers to equip their technical arsenal with an interchangeable patch‐clamp/ERG system. Key points: Rod and cone photoreceptors convert light into electrochemical signals that are transferred to second order cells, initiating image‐forming visual processing. Electroretinograms (ERGs) can detect the associated light‐induced extracellular transretinal events, allowing for physiological assessment of cellular activity from morphologically intact retinas. We outline a method for economically configuring a traditional patch‐clamp rig for performing high signal‐to‐noise ex vivo ERGs. We accomplish this by incorporating various 3D printed components and by modifying existing light pathways in a typical patch‐clamp rig. This methodology provides an additional set of tools to labs interested in studying the physiological function of neuronal populations in isolated retinal tissue.